Update on the epidemiology of Paget's disease of bone. - Cooper, C; Harvey, N; Dennison, E; van Staa, T (2006)
Paget's disease of bone (PDB) is characterized by rapid bone remodeling and the formation of bone that is structurally abnormal. Recent studies have confirmed that both genetic and environmental factors are important in its etiology. Epidemiological studies in Europe and North America have revealed that PDB shows an increasing frequency of occurrence with age and is more prevalent among men than women. There is marked geographic variation in the prevalence of PDB throughout western nations, with the highest rates reported during the 1970s in Britain. Recent studies of the secular trends in PDB suggest declining rates in both prevalence and severity at diagnosis. Thus, the overall age/sex standardized prevalence rate in Britain during the period 1993-1995 was found to be 2.5% among men and 1.6% among women > or = 55 years of age. Prevalence rates had fallen by approximately 50% in several of the centers studied, suggesting an environmental contribution to the etiology of this disorder. Similar findings have been reported from other European countries and New Zealand. Recent study of the incidence and clinical manifestations of PDB have emerged from large cohort studies in primary care record linkage resources, such as the General Practice Research Database. Over the period 1988-1999, the incidence rate of clinically diagnosed PDB was found to be 5 per 10,000 person-years among men and 3 per 10,000 person-years among women 75 years of age. The disorder was associated with an increased risk of back pain (RR, 2.1; 95% CI, 1.9-2.3); osteoarthritis (RR, 1.7; 95% CI, 1.5-1.9); and fracture (RR, 1.2; 95% CI, 1.0-1.5). Using life table methodology, the estimated proportion of patients dying within 5 years of follow-up was 32.7% among the cohort with PDB compared with 28.0% among control patients (p < 0.05).